Ferroptosis and its potential role in gestational diabetes mellitus: updated evidence from pathogenesis to therapy - Zhao, Yan; Gao, Qianqian; Li, Baoxuan; Wang, Yang; Wang, Yue (Frontiers in Endocrinology, 2023)
Background: Studies have demonstrated that high iron status is positively associated with gestational diabetes mellitus (GDM), implying that iron overload and ferroptosis play important roles in the development of GDM. The aim of this study was to explore effective therapeutic drugs from traditional Chinese medicine (TCM)formulas for the treatment of GDM based on ferroptosis.In this study, the presence of ferroptosis in the placenta was verified through clinical and experimental data, and key genes were subsequently screened for association with ferroptosis in the development of GDM. The analysis was based on transcriptome sequencing of datasets combined with differentially expressed genes (DEGs) analysis and weighted gene correlation network analysis (WGCNA); functional enrichment analysis was also performed. A proteinprotein interaction (PPI) network was constructed and pivotal genes were identified using Cytoscape. Finally, traditional Chinese medicine (TCM)formulas related to treating GDM were collected, then the proteins corresponding to the key genes were molecularly docked with the small molecular structures of clinically proven effective herbal tonics, and molecular dynamic simulations were performed to select the best candidates for pharmacological compounds.Results: Elevated ferritin levels in patients with GDM were verified using clinical data. The presence of ferroptosis in placental tissues of patients with GDM was confirmed using electron microscopy and western blotting. Ninety-nine key genes with the highest correlation with ferroptosis were identified from DEGs and weighted gene co-expression network analysis (WGCNA). Analysis using the Kyoto Encyclopedia of Genes and Genomes demonstrated that the DEGs were primarily involved in the oxidative phosphorylation pathway. The key genes were further screened by PPI; two key genes, SF3B14 and BABAM1, were identified by combining the gene corresponding to protein Ferroptosis in GDM 2 structure and function, followed by molecular docking and molecular dynamic simulation. Coptis chinensis was proposed as the best candidate for herbal treatment at the molecular level.Ferroptosis has an important role in the development of GDM.This data identified possible modulatory roles of ferroptosisrelated genes involved in the molecular mechanisms providing new insights into the pathogenesis of GDM,which also provided new directions for the systematic optimization of TCM formulas for the management and targeted treatment of GDM.